2013
DOI: 10.1111/jns5.12040
|View full text |Cite
|
Sign up to set email alerts
|

Two novel MPZ mutations in Chinese CMT patients

Abstract: To investigate the myelin protein zero (MPZ) gene mutation and related clinical features in Chinese Charcot-Marie-Tooth (CMT) patients, we screened the coding sequence of MPZ in 70 unrelated CMT index patients after excluding the PMP22 duplication, Cx32 and MFN2 mutations. We found four different missense mutations: c.194C>T, c.242A>T, c.371C>T, and c.419C>G. The frequency of MPZ mutation was approximately 4.35% of the total, 3.08% of CMT1, and 6% of CMT2. Mutations c.242A>T and c.419C>G are novel. The mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
8
1
1
Order By: Relevance
“…We searched the PubMed database using the terms "MPZ" and "Chinese" and excluded patients who may have been associated with previous reports based on the research team and publication time. We then summarized the MPZ mutational spectra and clinical characteristics of 35 families of unrelated Chinese origin (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The total mutations summarized in the Chinese patients with MPZ mutations are shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We searched the PubMed database using the terms "MPZ" and "Chinese" and excluded patients who may have been associated with previous reports based on the research team and publication time. We then summarized the MPZ mutational spectra and clinical characteristics of 35 families of unrelated Chinese origin (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The total mutations summarized in the Chinese patients with MPZ mutations are shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the spectra and frequencies of MPZ mutations in Caucasian and Japanese cohorts are different (7). Several studies have reported Chinese patients with MPZ mutations, but it is currently unknown whether there are differences in the spectra of MPZ mutations between Chinese and other ethnicities (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Herein, we report the mutational spectrum and clinical features of six unrelated Chinese families with MPZ in our hospital over a 7 years period.…”
Section: Introductionmentioning
confidence: 93%
“…To date, more than 240 different MPZ mutations have been identified (http://www.hgmd.cf.ac.uk/ ac/gene.php?gene=MPZ). MPZ mutations account for ~5% of patients with CMT and are the fourth most common genotype of CMT [5,11,12]. The natural history and genotype-phenotype correlations of MPZ-related neuropathies in the Chinese population remain entirely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Three were classifi ed as intermediate CMT with mMNCVs ranging from 32.8 to 45 m/s [26] . It has been suggested that MPZ is the second most frequent gene resulting in intermediate CMT (Table 2).…”
Section: Electrophysiological and Pathological Studies In This Englishmentioning
confidence: 99%